Cone-Beam Computed Tomography Assessment of Quality of Endodontic Treatment and Prevalence of Procedural Errors in Mandibular Molars - Ahmad Nouroloyouni; Amin Salem Milani; Ata Etminan; Sara Noorolouny; Elham Tavakkol; Hesam Mikaieli Xiavi; Nazila Ghoreishi Amin (International Journal of Clinical Practice)
Objectives. This study assessed the quality of endodontic treatment and the prevalence of procedural errors in permanent mandibular molars using cone-beam computed tomography (CBCT). Materials and Methods. This cross-sectional study was conducted on 328 CBCT scans (182 females and 146 males) of endodontically treated mandibular molars retrieved from the archives of two radiology centers in Ardabil city, Iran, in 2019. Mandibular molars were evaluated on sagittal, coronal, and axial sections regarding obturation length, obturation density (voids), missed canals, broken instruments, apical perforation, strip perforation, ledge formation, transportation, root fracture, root resorption, and periapical lesions by a senior dental student under the supervision of an oral and maxillofacial radiologist and an endodontist. Differences between the frequency of procedural errors and tooth type and gender were analyzed by the chi-square test. Results. The frequency of underfilling, missed canals, overfilling, voids, apical perforation, transportation, ledge formation, broken instruments, root fracture, strip perforation, root resorption, and periapical lesions was 34.8%, 17.4%, 16.8%, 14.3%, 7.3%, 6.1%, 4.3%, 3%, 1.2%, 0.6%, 5.5%, and 46%, respectively. The frequency of root fracture was significantly higher in females than in males P<0.05. The prevalence of underfilling was the highest in right second molars (47.2%), followed by right first molars, left second molars, and left first molars P<0.005. The frequency of transportation was maximum in right first molars (10%), followed by right second molars, left first molars, and left second molars P<0.04. Conclusion. Underfilling, missed canals, and overfilling were the most prevalent procedural errors in mandibular molars in our study population.